2021
DOI: 10.3390/jcm10112462
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Potential Risk Factors and Pulmonary Embolism in Sarcoidosis Patients Timely Treated

Abstract: Background. Some studies with inconclusive results have reported a link between sarcoidosis and an increased risk of pulmonary embolism (PE). This study aimed at assessing a possible correlation between potential risk factors and PE in sarcoidosis patients. Methods. A total of 256 sarcoidosis patients (84 males and 172 females; mean age at diagnosis 49 ± 13) were enrolled after giving written informed consent. Clinical evaluations, laboratory and radiology tests were performed to evaluate the presence of pulmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 35 publications
2
30
0
Order By: Relevance
“…A total of 44 consecutive patients, who had been admitted to the Respiratory High-Dependency Unit (RHDU) of the University Hospital of Trieste between 1 October 2020 and 30 November 2020 with a SARS-CoV-2 infection, demonstrated by a positive reverse transcriptase polymerase chain reaction (RT-PCR) test on either a nasopharyngeal swab or bronchoalveolar lavage, were retrospectively retrieved. Any patients with (i) a previous clinical history of lung disease; (ii) age < 18 years; or (iii) inadequate HRCT due to motion artifacts were excluded from the study [11][12][13][14]. Inclusion criteria were: (1) SARS-CoV-2 positive (on swab or bronchial wash); (2) age > 18 years and <80 years; (3) PaO 2 :FiO 2 < 250 mmHg; (4) bilateral infiltrates at chest radiography; (5) CRP > 100 mg/L; and/or (6) diagnosis of acute respiratory distress syndrome (ARDS) according to the Berlin definition during hospitalization; and (7) at least one HRCT performed within 3 months after hospital discharge as an alternative to criteria (4) and (5) [11][12][13][14].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 44 consecutive patients, who had been admitted to the Respiratory High-Dependency Unit (RHDU) of the University Hospital of Trieste between 1 October 2020 and 30 November 2020 with a SARS-CoV-2 infection, demonstrated by a positive reverse transcriptase polymerase chain reaction (RT-PCR) test on either a nasopharyngeal swab or bronchoalveolar lavage, were retrospectively retrieved. Any patients with (i) a previous clinical history of lung disease; (ii) age < 18 years; or (iii) inadequate HRCT due to motion artifacts were excluded from the study [11][12][13][14]. Inclusion criteria were: (1) SARS-CoV-2 positive (on swab or bronchial wash); (2) age > 18 years and <80 years; (3) PaO 2 :FiO 2 < 250 mmHg; (4) bilateral infiltrates at chest radiography; (5) CRP > 100 mg/L; and/or (6) diagnosis of acute respiratory distress syndrome (ARDS) according to the Berlin definition during hospitalization; and (7) at least one HRCT performed within 3 months after hospital discharge as an alternative to criteria (4) and (5) [11][12][13][14].…”
Section: Methodsmentioning
confidence: 99%
“…Any patients with (i) a previous clinical history of lung disease; (ii) age < 18 years; or (iii) inadequate HRCT due to motion artifacts were excluded from the study [11][12][13][14]. Inclusion criteria were: (1) SARS-CoV-2 positive (on swab or bronchial wash); (2) age > 18 years and <80 years; (3) PaO 2 :FiO 2 < 250 mmHg; (4) bilateral infiltrates at chest radiography; (5) CRP > 100 mg/L; and/or (6) diagnosis of acute respiratory distress syndrome (ARDS) according to the Berlin definition during hospitalization; and (7) at least one HRCT performed within 3 months after hospital discharge as an alternative to criteria (4) and (5) [11][12][13][14].…”
Section: Methodsmentioning
confidence: 99%
“…The risk factors associated with the onset of CTEPH reported in the literature include aspects related to the acute embolic event, the presence of some conditions associated with thrombophilia, and some concomitant pathological conditions [ 53 , 54 , 55 , 56 , 57 , 58 ]. Pengo et al identified the presence of previous episodes of PE or deep vein thrombosis (DVT) as risk factors for CTEPH, they are also reported that the greater extent of the initial embolic perfusion defect and the idiopathic presentation of pulmonary embolism are involved in the CTEPH process [ 34 ].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Irregular (2–5 mm) nodules with perilymphatic predilection causing irregular micronodular thickening of fissures and interlobular septa can be seen on HRCT. Parenchymal involvement can progress to irreversible disease manifesting as mid- to upper lung reticular opacities radiating from the hila ( Figure 2 C) [ 13 , 14 , 18 , 19 , 20 ].…”
Section: Autoimmune/inflammatory Disorders and Vasculitidesmentioning
confidence: 99%